PELATIHAN PENYUSUNAN MEDIA PEMBELAJARAN BERBASIS E-MODUL BAGI GURU DI SMP NEGERI 4 KERINCI - Asep, Asep; Helmi, Dewilna; Ansiska, Paisal (Universitas Pattimura, 2022)
The tri dharma of higher education contains elements of teaching, research, and service that must be carried out by lecturers in higher education. Community service is a forum for lecturers to contribute to the community according to the field they are engaged in. Learning is an activity carried out to achieve the goals of learning itself. In the learning process, it does not only provide information from educators to students. However, learning must be prepared carefully, one of which is through the provision of interesting learning media and in accordance with the times. Community service activities carried out with the title of training in the preparation of e-module-based learning media for teachers. This training activity through community service (PKM) provides space for teachers to innovate in developing the quality of learning through the development of appropriate learning media. This activity also provides an overview for teachers in carrying out their obligations according to the policy, namely the implementation of the independent learning curriculum. Through this activity, data were collected descriptively by describing responses and feedback with the implementation of this activity, namely providing a positive response in media development with the aim of increasing the pedagogic competence of teachers for quality learning preparation